Burned out or engaged at work? The role of self‐regulatory personality profiles. (1st January 2021) - Smith, Claire E.; Barratt, Clare L.; Hirvo, Alexis
Abstract: Employees' responses to work demands are crucially related to their occupational well‐being. The present study aimed to identify Big Five personality profiles of working adults and examine their connection to two central responses to work stress: work engagement and burnout. Four latent personality profiles emerged (i.e., overcontroller, undercontroller, reserved and resilient) and, in line with Block (2002) self‐regulation theory, related differently to burnout and engagement. Specifically, both under‐ and overcontrollers experienced higher burnout and lower engagement, whereas resilient experienced higher engagement and lower burnout. Reserved profile members were low in both. The results suggest that management of healthy, engaged workers may be aided by consideration of personality profiles and that Block's self‐regulation theory may be a useful framework for connecting personality to occupational well‐being.